1995
DOI: 10.1155/s0962935195000020
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and inflammation

Abstract: During the last few decades it has been recognized that cell death is not the consequence of accidental injury, but is the expression of a cell suicide programme. Kerr et al. (1972) introduced the term apoptosis. This form of cell death is under the influence of hormones, growth factors and cytokines, which depending upon the receptors present on the target cells, may activate a genetically controlled cell elimination process. During apoptosis the cell membrane remains intact and the cell breaks into apoptotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 109 publications
2
73
1
3
Order By: Relevance
“…During the process of apoptosis, dying cells break into apoptotic bodies that are rapidly phagocytosed ; therefore, this type of cell death is not considered to be a cause of inflammation (2). However, previous studies revealed that programmed cell death also affects immunity and induces inflammation, and, in recent years, inappropriate cell death was shown to be involved in metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the process of apoptosis, dying cells break into apoptotic bodies that are rapidly phagocytosed ; therefore, this type of cell death is not considered to be a cause of inflammation (2). However, previous studies revealed that programmed cell death also affects immunity and induces inflammation, and, in recent years, inappropriate cell death was shown to be involved in metabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis of PMN differs from necrosis. During the onset of apoptosis, the organelles and the cytoplasmic membrane remain intact and the histotoxic content of granules is not released into the extracellular compartment [6,9,33]. Moreover, apoptotic PMN are promptly removed by the macrophages (MAC) before they can support the development of cellular damage [33].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the result of this study revealed that silibinin not only had noinhibitory effects on CXCR3, CCR5 and CCR7 genes expression, but also could increase significantly the expressionof these genes in a dose and time-dependent manner. Although there is no study in the literature to be compared with this study,but there is a report that thecellular and molecular mechanisms of silibinin function could be cell-cycle arrest and apoptosis, therefore, the only proposed mechanism for inducing the effects of silibinin in chemokine receptor gene expression might beapoptotic cell death which can play an important role in inflammatory processes and reduction inflammatory reactionsrelated tochemokines receptors genes expression 22 .…”
Section: Effects Of Silibinin On Cell Proliferationmentioning
confidence: 98%